Jacobsen catalyst as a cytochrome P450 biomimetic model for the metabolism of monensin A - Rocha, Bruno Alves; de Oliveira, Anderson Rodrigo Moraes; Pazin, Murilo; Dorta, Daniel Junqueira; Rodrigues, Andresa Piacezzi Nascimento; Berretta, Andresa Aparecida; Peti, Ana Paula Ferranti; de Moraes, Luiz Alberto Beraldo; Lopes, Norberto Peporine; Pospíšil, Stanislav; Gates, Paul Jonathan; Assis, Marilda das Dores (BioMed research international, 2014)
Monensin A is a commercially important natural product isolated from Streptomyces cinnamonensins that is primarily employed to treat coccidiosis. Monensin A selectively complexes and transports sodium cations across lipid membranes and displays a variety of biological properties. In this study, we evaluated the Jacobsen catalyst as a cytochrome P450 biomimetic model to investigate the oxidation of monensin A. Mass spectrometry analysis of the products from these model systems revealed the formation of two products: 3-O-demethyl monensin A and 12-hydroxy monensin A, which are the same ones found in in vivo models. Monensin A and products obtained in biomimetic model were tested in a mitochondrial toxicity model assessment and an antimicrobial bioassay against Staphylococcus aureus, S. aureus methicillin-resistant, Staphylococcus epidermidis, Pseudomonas aeruginosa, and Escherichia coli. Our results demonstrated the toxicological effects of monensin A in isolated rat liver mitochondria but not its products, showing that the metabolism of monensin A is a detoxification metabolism. In addition, the antimicrobial bioassay showed that monensin A and its products possessed activity against Gram-positive microorganisms but not for Gram-negative microorganisms. The results revealed the potential of application of this biomimetic chemical model in the synthesis of drug metabolites, providing metabolites for biological tests and other purposes.
Keywords: Mitochondria, Liver; jaterní mitochondrie; krysa rodu Rattus; Animals; biologické modely; monensin; oxidace-redukce; Antifungal Agents; Models, Biological; zvířata; antifungální látky; Bacteria; Oxidation-Reduction; Rats; Cytochrome P-450 Enzyme System; systém (enzymů) cytochromů P-450; Monensin